Meningkatkan Minat Pembelajaran PAI Melalui Teori Motivasi Pada Siswa Kelas VIII MTS Muhammadiyah Kampung Delima - Rukmini, Reni Dianti; Purnama Sari, Dewi; Warsah, Idi (UIN Fatmawati Sukarno Bengkulu, 2024)
Islamic Religious Education (PAI) has a very vital role in shaping the character, morals, and spiritual understanding of students. In addition to functioning as a means of providing religious knowledge, PAI also plays a role in instilling religious values that guide students in their daily lives. Various theories of motivation, including intrinsic and extrinsic motivation in building student motivation in increasing interest in learning PAI. The purpose of this study was to see the motivation of class VIII students of MTS. Muhammadiyah Kampong Delima in increasing interest in learning PAI. This study uses a qualitative research type. The results of the study indicate that motivation plays a very important role in influencing the behavior and achievement of an individual. Both in terms of intrinsic motivation and extrinsic motivation.